A Global Database to Monitor Annual Mangrove Forest Change, 2000-2020: GMC-21 - Hamilton, Stuart E; Presotto, Andrea (International journal of applied geospatial research, 2024)
This manuscript presents a new global database that tracks annual global mangrove forest change rates since 2000. By synthesizing several remotely sensed databases such as Mangrove Forests of the World, Global Mangrove Watch, and High-Resolution Global Maps of 21st-Century Mangrove Forest Cover Change, this database provides mangrove forest change information at approximately 30 m annually and globally. It is a consistent and systematic mangrove forest change database across all years. Between 2000 and 2020, mangrove forests lost 3.42% of their original global area, shrinking from approximately 139,716 km2 in 2000 to 134,383 km2 in 2020, resulting in an annual loss rate of 0.17%. As of 2020, Indonesia, Brazil, Australia, Nigeria, and Malaysia are the top five mangrove-holding countries, containing slightly over 50% of the global mangrove holdings. Indonesia alone contains 22% of global mangrove forests.